Life cycle and circularity metrics to measure the sustainability of closed-loop agri-food pathways - Giacomo Falcone; Teodora Stillitano; Nathalie Iofrida; Emanuele Spada; Bruno Bernardi; Giovanni Gulisano; Anna Irene De Luca (Frontiers in Sustainable Food Systems, 2022)
This work aims to present a methodological proposal based on Life Cycle (LC) methodologies, and circularity performance indicators, to assess closed-loop pathways by providing comprehensive results on economic and environmental impacts generated by agri-food production systems. The methodological approach will be tested on olive oil production systems, one of the most important agri-food chains for Mediterranean countries, whose import and export significance is set to grow in light of the shrinking market supply of seed oils. Some insights for the co-products valorization are provided through the evaluation of the reuse of by-products as a possible resource capable to improve the sustainability of the olive oil farms. The integrated application of three different methodologies, Life Cycle Assessment (LCA), Environmental Life Cycle Costing (ELCC) and Material Circularity Indicator (MCI), enabled comparative evaluation of Extra Virgin Olive Oil (EVOO) production under a linear production model with production under a circular model. The circular scenario was better in most environmental impact categories, registering an improvement in Global Warming Potential (GWP) of nearly 30%. In economic terms, there was a lower production cost for the circular scenario and a lower environmental cost by reducing the use of synthetic products through the reuse of waste products. The circular scenario recorded a higher degree of circularity due to a reduction in virgin raw materials used in the production process and a reduction in non-recoverable waste. The implementation of circular strategies represents one of the possible trajectories to guide the ecological transition, and the proposed methodological framework can support the decisions of both producers and public decision-makers toward more sustainable and efficient production patterns.